Suicide Death and Post-suicide Cultural Practices in Southwest Nigeria: Implications for Suicide Reporting - ABORISADE, Richard Abayomi; BAWALLA, Oluwatoyin Gbenga; OYAFUNKE-OMONIYI, Comfort Oyinlola; AKINDELE-OSCAR, Yomi; ADELEKE, Oladele Adelere; OLAYINKA-ALIU, Damilola Adepeju; ADENUGA , Ademolu Oluwaseun; ADEYEMO, Sunday Oladotun (Dhaulagiri Journal of Sociology and Anthropology, 2023)
Indeed, the underreporting of suicides and misclassification of causes of death has been acknowledged as a serious global concern among scholars and policymakers, especially in low and middle-income countries (LMIC). While studies have identified the criminal status of suicide as a factor responsible for the low reporting of suicide cases in Nigeria, religious and sociocultural underpinnings of suicide reporting have been ignored. This study, therefore, explores the social interpretations and cultural practices involved in handling suicide cases in 30 selected communities in southwest Nigeria. This is to unravel how these practices impact suicide reporting in the selected region. Purposive sampling was used to reach out to 90 traditional rulers, religious priests, and opinion leaders in the selected communities. The narratives of the study participants revealed that suicide is socially perceived as an abominable way to die, a revolt against one’s destiny, and a protest against the gods. Communities are in awe of the spiritual import of suicide deaths, which often informs the harsh treatment of bodies of suicide victims and secondary victimization of bereaved families, with implications for suicide reporting. The study suggests aligning cultural practices with the formal methods of handling suicide.